2018
DOI: 10.1103/physreva.98.021401
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism in high-order harmonic generation from chiral molecules

Abstract: In this study, circularly polarized high harmonic generation (CP-HHG) from a chiral molecule, limonene, by a CP counter-rotating two-color laser field was found to possess circular dichroism. A high harmonic spectrum from a limonene enantiomer depends on the combination of the chirality of the enantiomer and the rotation direction of the superimposed two-color laser field in comparison with that of an achiral atom, helium. From R-enantiomer, the harmonic orders with clockwise polarization were generated more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…This approach is general and can be applied via an infinite set of geometries [i.e., our suggested schemes (A), (B), and (C) are representative.] Remarkably, the technique results in extremely high chiral/achiral sensitivity of up to 99%, which outperforms, by far, the ability of previous cHHG techniques to discern chiral media [28][29][30][31][32][33]. It also allows direct access to the medium's handedness by measuring the harmonic's helicities, which change sign when the medium's handedness is switched.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This approach is general and can be applied via an infinite set of geometries [i.e., our suggested schemes (A), (B), and (C) are representative.] Remarkably, the technique results in extremely high chiral/achiral sensitivity of up to 99%, which outperforms, by far, the ability of previous cHHG techniques to discern chiral media [28][29][30][31][32][33]. It also allows direct access to the medium's handedness by measuring the harmonic's helicities, which change sign when the medium's handedness is switched.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, it was also discovered that high harmonic generation (HHG) with a helically polarized pump is chirality sensitive [28][29][30][31][32][33]. In chiral HHG (cHHG), a chiral medium is irradiated with an intense laser field, and the emission spectrum is measured.…”
Section: Introductionmentioning
confidence: 99%
“…[39], Fleischer et al reported on the observation of a 30%-chiral effect. Using an experimental scheme based on the detection of photoelectrons generated in a krypton gas target employing BHHG radiation, Harada et al [40] found a pronounced difference in the responses of the (R) and the (S) enantiomers of gas-phase limonene.…”
Section: Introductionmentioning
confidence: 99%
“…HHG has been theoretically studied for decades using a variety of methods [15][16][17][18][19]. Over the last few years, as both the theoretical and experimental attoscience shifts towards increasingly more complex systems including solids [20,21] and biomolecules [22][23][24], the real-time propagation of the wavefunction using time-dependent * awozniak@chem.uw.edu.pl quantum chemical methods coupled to L 2 -integrable basis sets have gained some recognition in describing the electron dynamics during attosecond processes [19,[25][26][27][28]. Due to a better scaling with the number of electrons and much easier handling of multicenter systems, they are slowly surpassing the purely numerical, grid-based approaches.…”
Section: Introductionmentioning
confidence: 99%